2022
DOI: 10.1039/d2qi00275b
|View full text |Cite
|
Sign up to set email alerts
|

Large easy-axis magnetic anisotropy in a series of trigonal prismatic mononuclear cobalt(ii) complexes with zero-field hidden single-molecule magnet behaviour: the important role of the distortion of the coordination sphere and intermolecular interactions in the slow relaxation

Abstract: The complexes [Co(L)]X·S (X = CoCl42- , S = CH3CN (1); X = ZnCl42- , S = CH3OH (2)), [Co(L)]X2·S (X = ClO4-, S = 2CH3OH (3) and X =...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 111 publications
3
34
0
Order By: Relevance
“…By keeping the energy barrier fixed to U eff = 85 cm −1 (corresponding to ( S 2 − 1/4)| D | = 2| D |, for S = 3/2 using the experimental value of D = −42.6(4) cm −1 ), the remaining parameters were obtained as C = 0.040(9) K − n s −1 , n = 5.1(1) and τ 0 = 2.1(1) × 10 −9 s, where n is within the values calculated for other Co( ii ) complexes reported in the literature. 8,10,17…”
mentioning
confidence: 99%
“…By keeping the energy barrier fixed to U eff = 85 cm −1 (corresponding to ( S 2 − 1/4)| D | = 2| D |, for S = 3/2 using the experimental value of D = −42.6(4) cm −1 ), the remaining parameters were obtained as C = 0.040(9) K − n s −1 , n = 5.1(1) and τ 0 = 2.1(1) × 10 −9 s, where n is within the values calculated for other Co( ii ) complexes reported in the literature. 8,10,17…”
mentioning
confidence: 99%
“…Out of curiosity, we included the extended double d-shell in the active space CAS(7,10) and found a consistent positive sign of D both in CASSCF and NEVPT2 calculations (Table S4 in SI). To come to an end, it has been deduced that the dynamical correlations play major role in determining the accurate sign of D. Additionally, the extended double d-shell in active space may also be advantageous to have consistent sign of D. This kind of ambiguity has been reported by Singh et al 54 earlier and by Gereka et al 31 only recently suggesting the requirement of specific theoretical calculations or the experimental techniques like HFEPR to determine the magnetic anisotropy for this kind of complex reliably. The lowest spin-free energies for all the complexes along with the corresponding contribution to D and E values are enlisted in Table 3.…”
Section: Zfs Parametersmentioning
confidence: 91%
“…Besides, this Co(II) system owing to Kramers ground state, is presumed not to relax largely via direct and under-the-barrier QTM process, in the vicinity of zero external magnetic field. 31 Consequently, it is deduced to have slow magnetic relaxation, likely in absence of any field, and is anticipated to demonstrate magnetic hysteresis. The number at each arrow corresponds to mean absolute value of the corresponding matrix element of the transition magnetic moment.…”
Section: Magnetic Relaxation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Far-IR magneto-spectroscopy (FIRMS) , and frequency-domain Fourier transform terahertz EPR are two other direct methods to determine magnetic excited states, including a recent work by Lu, Nelson, and co-workers using terahertz time-domain EPR through a simple tabletop approach to probe the transitions between the spin levels in transition-metal complexes . Brackett and Richards have shown that electronic spin transitions (Δ m S = 0, ±1) between the ground and the excited KDs (Figure ) are magnetic-dipole-allowed by symmetry and selection rules in far-IR spectroscopy. , FIRMS has been used to study transitions between the two KDs, ,, , giving, e.g., the energy gap 2 D ′ = 2­( D 2 + 3 E 2 ) 1/2 in S = 3/2 complexes. For high-spin Co II complexes with large ZFS (>30 cm –1 ), HFEPR operating in the sub-THz frequency range gives E / D ratio and g values. ,,,, The combined use of FIRMS, EPR, and inelastic neutron scattering (INS) has been adopted recently to give ZFS parameters for such complexes. ,,,, This approach is still at its early stage, requiring additional studies to understand its scope and applicability.…”
Section: Introductionmentioning
confidence: 99%